(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Dialium guineense have been shown to possess medicinal properties and its parts are used to treat different ailments. The present study investigated the toxic responses of the blood of rats exposed to subchronic doses of aqueous extract of Dialium guineense stem bark. Thirty-five (35) rats of Wistar strain (160 to 180 g) were divided into seven groups of 5 rats each. Group I served as control, while rats in the other groups were administered varied doses of extract (200 - 5000 mg/kg body weight, bwt) orally for 28 days. Haematological indices of rat blood were analysed using haematological Swelab autocounter 920E+ (UK) system. The results showed that graded doses of aqueous extract of D. guineense stem bark did not significantly alter the concentrations of the measured haematological parameters (p > 0.05). These results indicate that aqueous extract of the medicinal plant has no deleterious effect on haematopoietic system of rats.